Scientific advances in headache research: an update on neurostimulation. (January 2013) - Hoffmann, Jan; Magis, Delphine
3rd European Headache and Migraine Trust International Congress London, UK, 20–23 September 2012 The pathophysiological understanding of migraine and other primary headaches has been substantially improved over the last 20 years. A milestone that paved the way for successful research was the development of the International Classification of Headache Disorders published by the International Headache Society in 1988. The classification facilitated a clear clinical diagnosis of headache disorders and allowed research efforts to be focused on clearly defined syndromes. Recent advances in the understanding of headache disorders have been driven by the availability of new research tools, such as advanced imaging techniques, genetic tools, pharmaceutical compounds and devices for electrical or magnetic stimulation. The latest scientific and clinical advances were presented at the recent European Headache and Migraine Trust International Congress (EHMTIC) in London (UK).